Radiographic imagery of aggressive plexiform-type ameloblastoma in the mandible: a case report - Arnawansah, Rakhmat Putra Guru; Yunus, Barunawaty; Rahman, Fadhlil Ulum Abdul; Ariestiana, Yossy Yoanita; Mubarak, Husni (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: This case report aims to describe the radiographic characteristics of plexiform ameloblastoma and its impact on surrounding tissues in a middle-aged female patient using panoramic radiography and CBCT, along with case management. Case Report: A 43-year-old female patient presented to the Dental Radiology Unit of RSGMP UNHAS with a panoramic referral letter, diagnosed clinically with anterior mandibular ameloblastoma. Extraoral examination revealed an asymmetrical facial appearance with anterior mandibular enlargement. Intraoral examination showed mucus membrane enlargement in the anterior mandible region (teeth 37-45), soft consistency, absence of crepitus, no palpation tenderness, and mobility in several anterior mandibular teeth. The first panoramic radiograph (March 16, 2022) exhibited a unilocular radiolucent lesion, well-defined, with scalloped margins in the anteroposterior mandibular region. The second panoramic examination (May 23, 2022) indicated a more aggressive lesion expansion, with evidence of root resorption and destruction of the inferior mandibular cortex approaching the mandibular angle. CBCT findings demonstrated a hypodense/radiolucent lesion extending anteroposteriorly, superiorly, and inferiorly, leading to displacement, root resorption, and destruction of the inferior mandibular cortex in the inferior direction. Conclusion: Based on the characteristics and structure of the lesion observed through various radiographic examinations, a unilocular ameloblastoma was suspected. Histopathological examination confirmed the plexiform-type ameloblastoma.